OC-003 Efficacy and Safety of Golimumab Induction for Moderate to Severe Ulcerative Colitis in the United Kingdom: Results from the Go-Colitis Study. (17th August 2016) - Probert, C; Gaya, D; Hamlin, PJ; Irving, P; Sebastian, S; Gillespie, G; Tate, H; Wheeler, C
Abstract : Introduction: Induction and maintenance of clinical response is a treatment goal for ulcerative colitis (UC). GO-COLITIS (NCT02092285 ; 2013–004583-56) is a UK phase 4, multicentre, open-label, single-arm trial evaluating the efficacy of golimumab (GLM) in induction and maintenance of clinical response in patients with moderate to severe UC. We report the results of an interim analysis of clinical response at the end of the GLM induction phase. Methods: Anti-TNF naive patients (≥18 y) with UC ≥ 3 months and with moderate to severe disease (partial Mayo score 4–9 or Mayo score 6–12) at baseline, Mayo rectal bleeding subscore ≥1, and Mayo endoscopy subscore ≥2 (if full Mayo was used) were included. Patients received SC GLM on day 0 (200 mg) and day 14 (100 mg) during the 6 week induction phase, followed by GLM 50 or 100 mg every 4 weeks during the 48 week maintenance phase with 12 week follow-up, in line with the Summary of Product Characteristics. Clinical response and remission were summarised descriptively at the end of week 6. Clinical response was defined as decrease in partial Mayo score of ≥2 points and ≥30% from baseline, plus either a decrease in rectal bleeding subscore of ≥1 point or an absolute rectal bleeding score ≤1. Patients without scores were considered nonresponders. Clinical remission was defined as partial Mayo score ≤2 and no individual Mayo subscore >1. Results: 205 patients were enrolled (mean [range] age, 39.3 [18–79] years; male, n = 123 [60%]). The mean baseline (SD) partial Mayo score was 6.4 (1.4). All patients received one or two doses of induction GLM. Clinical responses occurred in 141/205 patients (response rate, 68.8%; 95% CI, 62.0%–75.1%). Clinical remission occurred in 79/205 patients (remission rate, 38.5%; 95% CI, 31.8%–45.6%). The mean (SD) change from baseline in partial Mayo score (n = 198) was –3.2 (2.4). AEs (any cause) occurred in 37 (18%) patients. Serious AEs occurred in 17 (8%) patients: UC flare/worsening (n = 11), accidental overdose (n = 2), anaphylaxis (n = 1), constipation (n = 1), rectal fissure (n = 1), and respiratory tract infection (n = 1). Eight patients (4%) discontinued due to serious AEs. There were no fatal AEs. Conclusion: During the GLM induction phase of GO-COLITIS, 68.8% of patients had a partial Mayo response and were eligible to continue to the 48 week maintenance phase. AEs were consistent with previous observations; no new safety signals were identified. Disclosure of Interest: C. Probert Consultant for: Abbvie, MSD, Napp, Takeda, Speaker bureau with: Abbvie, Falk, Ferring, MSD, Shire, Takeda, Conflict with: Abbvie, Falk, MSD, Shire, Takeda, D. Gaya Speaker bureau with: Abbvie, Falk, Ferring, MSD, Shire, Takeda, Vifor, Conflict with: Abbvie, Falk, Ferring, MSD, Shire, Takeda, Vifor, P. Hamlin Speaker bureau with: Abbvie, Ferring, MSD, Takeda, Tillotts, Warner Chilcott, Conflict with: Abbvie, Falk, MSD, Tillotts, P. Irving Grant/research support from: MSD, Takeda, Consultant for: Abbvie, MSD, Takeda, Warner Chilcott, Vifor Pharma. Pharmacosmos, Topivert, Genentech, Hospira, Speaker bureau with: Abbvie, Falk Pharma, Ferring, MSD, Takeda, Warner Chilcott, Johnson and Johnson, Shire, S. Sebastian Grant/research support from: Abbvie, Ferring, Warner Chilcott, Consultant for: Falk Pharma, Ferring, MSD, Takeda, Warner Chilcott, Vifor Pharma, Speaker bureau with: Abbvie, Takeda, Warner Chilcott, G. Gillespie Shareholder of: MSD UK, Conflict with: Employment MSD UK, H. Tate Consultant for: MSD UK, C. Wheeler Shareholder of: MSD UK, Conflict with: Employment MSD UK